Substantiation of Innovative Development Prospects for Grain Production in Kazakhstan - UMAROV, Ilkhom Mirsabitovich (Journal of Advanced Research in Law and Economics, 2017)
In the context of globalization and increasing international competition, the innovative way of development has no alternatives. The article analyzes the performance and main issues of the grain industry development in the Republic of Kazakhstan. The author concludes that presently in Kazakhstan, the innovative activity in the sector of grain production has increased and the structure of agricultural science has been formed to provide for functionality according to the ‘research - experimental works - practical implementation of the results’ model. The author has determined the promising lines of innovative development of grain production that would provide improvement of the agricultural sector efficiency in Kazakhstan. First and foremost, the changes must be introduced in the number of manufacturing processes that as a result will contribute to the development of the seed production, implementation of the advanced technologies in agriculture, enhancement of the functioning efficiency of the system of land reclamation and irrigation, introduction of the resource-saving technologies in agriculture, construction of the modern grain elevators, and development of the innovative grain storage technologies.